Strategies to promote health literacy from primary care: a perspective that considers the realities of low and middle-income countries - Málaga, German (2019)
Health literacy is associated with better health outcomes. Primary care professionals generally provide most of the care to patients and are also often the first point of contact for patients within a health system. This article discusses four strategies to promote health literacy in the primary care setting: 1) Improve the clinician’s communication skills, 2) Use e-Health tools, 3) Promote patient self-care, and 4) Develop support systems and care environments. These strategies are discussed in the context of the realities of low and middle income countries, as in the case of Peru.